EDUKASI LINGKUNGAN MELALUI MEDIA PLANG UMUR SAMPAH DALAM MENINGKATKAN KESADARAN MASYARAKAT - Muasomah; Khumaerotun Nisya (CV. Kalimasada Group, 2026)
Waste management remains a significant environmental issue in society, including in Ambokembang Village, Kedungwuni District, Pekalongan Regency, Central Java. The low level of public awareness regarding waste types and decomposition periods has resulted in suboptimal waste management practices. This community service activity aimed to improve environmental awareness through the utilization of educational media in the form of waste decomposition signboards (plang umur sampah). The methods used included preliminary observation, media design, production and installation of signboards at strategic locations, as well as community socialization activities. The results showed that the waste decomposition signboards were able to enhance community understanding regarding the impacts of waste and the importance of proper waste management. The community responded positively to this activity, as indicated by increased attention to environmental cleanliness and reduced littering behavior. Therefore, the use of waste decomposition signboards is considered effective as an environmental education medium at the community level.